Shadowing and anisotropy of solar energetic ions at Mars measured by MAVEN during the March 2015 solar storm. Issue 4 (15th April 2016) - Lillis, Robert J.; Lee, Christina O.; Larson, Davin; Luhmann, Janet G.; Halekas, Jasper S.; Connerney, Jack E. P.; Jakosky, Bruce M.
Abstract: The Solar Energetic Particle (SEP) Instrument on the Mars Atmosphere and Volatile EvolutioN (MAVEN) spacecraft is meant to characterize the variability of SEP fluxes at Mars. SEP ion precipitation is an important source of heating, ionization, and chemical changes in the upper atmosphere of Mars and may have played a substantial role in driving atmospheric escape over the history of the solar system. Here we examine SEP fluxes during a series of solar disturbances in late February through early March 2015. We present the first SEP ion pitch angle distributions measured at Mars and show how SEP anisotropy changes over the course of the event period. We present examples and explanations of several different kinds of variability in the SEP flux measured in the four fields of view of the instrument. Finally, we present a statistical study of energy‐ and angle‐dependent shadowing of SEP under three different sets of heliospheric conditions, showing that the direct shadowing of SEP by the solid planet may be better explained in terms of simple geometry under quieter heliospheric conditions. In‐depth understanding of the effects on SEP fluxes and precipitation patterns by the complex interplay between solar wind disturbances and Mars' magnetospheric configuration awaits detailed modeling studies. Key Points: Pitch angle anisotropy of SEP ions at Mars varies with heliospheric conditions Variability in MAVEN SEP ion measurements has several different nonheliospheric causes Blockage (i.e., shadowing) of energetic ions by Mars is energy dependent and highly variable